Leitura empírica do céu de Caiçara: uma abordagem metodológica para o ensino de astronomia em uma escola do campo - Santos, Fabiana Gomes (2019)
This research proposes to elaborate and apply a teaching proposal that enables a contextualized education, in the Escola Municipal Manoel José Vitorino da Silva, in its only working room, which attends students of early childhood education (4 and 5 years) and Initial grades of elementary school (6 to 14 years), being configured as multiseriated. This proposal intends to address the concepts of astronomy present in the science curriculum, having as a starting point the Cultural astronomy. For this, it was necessary to survey the local knowledge of the Sertanejos and the Sertanejas, residents of the village of Caiçara, located in the municipality of Capim Grosso-Ba, from their readings of heaven, analyzing how these knowledge influenced and Continue to influence their practical activities such as agriculture and animal husbandry, promoting better productivity, as well as in their daily lives. As a method of research to access this local knowledge, we used Oral history, since these knowledgeknowledge is transmitted throughout the generations by oral and bodily expressions. After the survey of these knowledges and analyses, data were generated for the elaboration of educational products, such as the literary text in the format of the tale "The Stars of the Imbus", which uses an accessible and common vocabulary for the students of the locality. This tale triggered a didactic sequence-SD of interdisciplinary character, based on the foundations of the national common Curricular Base-BNCC. In order to promote the diffusion of astronomy not only in the system of formal education, we present as actions of the SD the mobile planetarium in the school, with the presence of the astronomer and co-advisor of the research, Professor Dr. Marildo Pereira, enabling the Visitation Daytime for students and nocturnal for the community, as well as the observation of Heaven with its telescope in a public square, fostering, in addition to the diffusion of astronomy, the dialogue between local knowledge and scientific knowledge of higher education institutions, such as the university State of Feira de Santana - UEFS.